The Rise of Euroskepticism : Europe and Its Critics in Spanish Culture - Martín-Estudillo, Luis (Book collections on Project MUSE., 2017)
"This book deals with the role that artists and intellectuals have had regarding projects of European integration. Taking Spain as a case study, the book analyzes how their works offer nuanced and engaging perspectives on the emotions generated by the ideal of a unified Europe and its most recognizable embodiment, the European Union (EU). The sustained scrutiny of the ever-evolving idea of Europe by artists and intellectuals has helped to pave the way for the current widespread protests against the EU. Consciously or not, they partake of a tradition of Euroskepticism. In the book, Euroskepticism designates a constellation of attitudes and arguments that have developed in reaction to pan- and pro-European movements. Its evolving features are conditioned by culture and formed in discourse. Because Euroskepticism is often associated exclusively with the discourse of political elites, its literary and artistic expressions have gone largely unnoticed, because their complex contributions escape academic approaches that prioritize other types of data. The book addresses this gap in the scholarship by examining closely a variety of Euroskeptic texts from a diachronic perspective, covering roughly from 1915 to the present. Knowing about this eclipsed critical tradition contributes to a deeper understanding of the notion of Europe and its institutional embodiments. It gives resonance to the intellectual and cultural history of Europe's "peripheries" and re-evaluates Euroskeptic contributions as one of the few hopes left to imagine ways to renew the promise of a union of the European nations"--